THE INVESTIGATION OF LISTENING COMPREHENSION PROBLEMS OF AMERICAN ACCENTS FOR IRANIAN B.A. STUDENTS OF TRANSLATION STUDIES - Nemati, Azadeh; Qareqani, Kamran; Fumani, Mohammad Reza Falahati Qadimi (Online Journal of Humanities ETAGTSU, 2016)
This study attempted to investigate the listening comprehension problems of American accents of B.A. students of English translation studies. To attain this objective their performance in TOEFL and IELTS (their listening comprehension sections) tests were checked. Further, they received a short, open-ended questionnaire to comment on their problems in listening comprehension. Based on the results, most of the students performed poorly on both TOEFL and IELTS (listening comprehension) tests. Further, most of the students (21 cases, 52.5%) asserted that their main problem was in „identifying words when they listened to an audio file, i.e. they were not used to fast speech‟. In all, 16 students (40%) announced that they were „weak at vocabulary and colloquial terms‟. So, it appeared that students had major problems in listening and in vocabulary and viewed these two elements as the main factors that hindered the listening comprehension process. Moreover, it was found that 45% (18 cases) of the participants believed that „insufficient attention to listening comprehension practices at the university‟ was responsible for their problems in listening comprehension. It appeared that universities should put more emphasis on listening comprehension problems. In fact, listening comprehension problems are a dominant one among language learners (Field, 1998). The findings in this thesis could be useful for language learners as well as language teachers. <a title="The Investigation of Listening Comprehension Problems of American Accents for Iranian B.A. Students of Translation Studies" href="https://etag.tsu.ge/journal/files/01_Azadeh-Nemati_etc..pdf" target="_blank" rel="noopener">Full Text (PDF)